Model Kepemimpinan Spiritual (Studi Kasus Pada BMT Mandiri Sejahtera dan BMT Al-Hikmah Semarang) - Sulton, Ahmad Shilbi, Muhammad Sholahuddin. . S.E,. M.Si S.E,. M.Si (2017)
This study aims to determine whether the vision, hope / faith, love altruistic, meaning / call, membership, commitment, job satisfaction influence on spiritual leadership, explain how much influence the vision, hope / faith, love altruistic, meaning / call, membership, commitment , job satisfaction on spiritual leadership and know how to fry on the model of spiritual leadership BMT Mandiri Sejahtera and BMT Al-Hikmah. Respondents in this study were employees BMT Mandiri Sejahtera and BMT Al-Hikmah which has become the employee during the year. Data analyzed using analysis of data quality (validity and reliability testing), classical assumption (normality test, multikoleniaritas, heteroscedasticity test, test autocorrelation), multiple linear regression, t-test, F test and coefficient of determination. t test results showed that the variables of vision, hope / faith, altruistic love, meaning, membership, commitment and job satisfaction significantly influence spiritual leadership. While the F test results showed that together on the variable vision, hope / faith, altruistic love, meaning, membership, commitment and job satisfaction have a significant influence on the spiritual leadership. And variable vision, hope / faith, altruistic love, meaning, membership, commitment and job satisfaction of the spiritual leadership has a number greater than the other vaiabel.